Parameters of Physical Performance of Qualified Football Players in the Preparatory Period of Training - Doroshenko, I.; Svatyev, A.; Sobol, E.; Danylchenko, S.; Doroshenko, E. Yu.; Дорошенко, І.; Сватьєв, А.; Соболь, Е.; Данильченко, С.; Дорошенко, Едуард Юрійович (My University, 2023)
The purpose of the work: to determine the level of physical fitness of qualified football players in the preparatory period of the annual macrocycle based on test indicators for the formation of rational programs for their preparation for competitive activities. Material and methods. Contingent: 25 qualified football players of MFC “Metalurg” (Zaporizhzhya): 15 athletes – application form “A” and 10 athletes – application form “B” of the second stage of the “Champion” group VBET UA 2022-2023 season of Professional Football League of Ukraine. Methods: Analysis and systematization of data from scientific and methodical literature and the electronic resource of global information network “Internet”; pedagogical observations; pedagogical testing: PWC170 (Physical Working Capacity); Harvard Step-Test; pedagogical experiment of controlling orientation; methods of mathematical statistics. Results. During the educational and training meetings, the test indicators had statistically significant differences in the direction of decreasing values of special physical capacity, from retractable microcycle to percussive microcycle (p<0,05): аPWC170 – 1469.33 ± 50.11 and 1377.67 ± 49.11 (kg•m•min-1), rPWC170 – 20.87 ± 0.69 and 20.71 ± 0.71 (kgm•min-1•kg-1), aVO2 max – 4002.23 ± 115.23 and 3857.54 ± 117.34 (ml•min-1), rVO2 max – 61.57 ± 1.51 and 54.37 ± 1.67 (ml•min-1•kg-1), in accordance. Also, during the educational and training meetings, the test indicators had statistically significant differences in the direction of increment values of special physical capacity: from percussive microcycle to submersible microcycle (p<0.05): аPWC170 – 1377.67 ± 49.11 and 1494.34 ± 51.78 (kg•m•min-1), rPWC170 – 20.71 ± 0.71 and 21.37 ± 0.85 (kgm•min-1•kg-1), aVO2 max – 3857.54 ± 117.34 and 3997.09 ± 114.89 (ml•min-1), rVO2 max – 54.37 ± 1.67 and 63.67 ± 1.71 (ml•min-1•kg-1), in accordance. Conclusion. The way to solve this problem is the proposed methodical approach, which allows, on the one hand, to comprehensively approach the solution of the issue of the complex orientation of the training process of qualified football players in the preparatory period of training, on the other hand, it provides for the differentiation of the team composition into typological groups of athletes, which allows to have a targeted influence on indicators of special physical capacity and technical and tactical potential of qualified football players. Мета роботи: визначити рівень фізичної підготовленості кваліфікованих футболістів у підготовчий період річного макроциклу за тестовими показниками для формування раціональних програм їх підготовки до змагальної діяльності. Матеріал і методи. Контингент: 25 кваліфікованих футболістів МФК «Металург» (Запоріжжя): 15 спортсменів – заявковий лист «А» і 10 спортсменів заявковий лист «В» до ІІ етапу групи «Чемпіон» VBET UA 2022-2023 сезону Професіональної Футбольної Ліги України. Методи: аналіз та систематизація даних науково-методичної літератури та електронних ресурсів глобальної інформаційної мережі «Інтернет»; педагогічні спостереження; педагогічне тестування: PWC170 (Physical Working Capacity); Гарвардський степ-тест; педагогічний експеримент контролюючої спрямованості; методи математичної статистики. Результати. Під час навчально-тренувальних зборів показники тестів мали статистично значущі відмінності у бік зменшення значень спеціальної фізичної працездатності з втягувального до ударного мікроциклу (р<0,05): аPWC170 – 1469,33±50,11 та 1377,67 ± 49,11 (кг•м•хв-1), rPWC170 – 20,87 ± 0,69 і 20,71 ± 0,71 (кгм•хв-1•кг-1), aVO2 max – 4002,23 ± 115,23 і 3857,54 ± 117,34 (мл•хв-1), rVO2 max – 61,57 ± 1,51 і 54,37 ± 1,67 (мл•хв-1•кг-1), відповідно. Також під час навчально-тренувальних зборів показники тестів мали статистично значущі відмінності за напрямом приросту значень спеціальної фізичної працездатності: від ударного до підвідного мікроциклу (p<0,05): аPWC170 – 1377,67 ± 49,11 і 1494,34 ± 51,78 (кг•м•хв-1), rPWC170 – 20,71 ± 0,71 і 21,37 ± 0,85 (кгм•хв-1•кг-1), aVO2 max – 3857,54 ± 117,34 і 3997,09 ± 114,89 (мл•хв-1), rVO2 max – 54,37 ± 1,67 і 63,67 ± 1,71 (мл•хв-1•кг-1), відповідно. Висновок. Шляхом реалізації мети дослідження є запропонований методичний підхід, який дозволяє, з одного боку, комплексно підійти до вирішення питання комплексної спрямованості тренувального процесу кваліфікованих футболістів у підготовчий період підготовки, з іншого боку, передбачається диференціація складу команди на типологічні групи спортсменів, що дозволяє цілеспрямовано впливати на показники спеціальної фізичної працездатності та техніко-тактичного потенціалу кваліфікованих футболістів.
Параметри фізичної роботоздатності кваліфік
Doroshenko E. Yu. - https://orcid.org/0000-0001-7624-531X
Keywords: football; qualification; training; special physical capacity; functional readiness; футбол; кваліфікація; підготовленість; спеціальна фізична працездатність; функціональна підготовленість